Hemoptysis in Madagascar: etiologies of 114 cases - Rakotoson, J L; Rakotondravelo, S J B; Rakotomizao, J R; Andrianarisoa, A C F (Médecine tropicale, 2010)
A prospective study of patients presenting hemoptysis was carried out over a 12-month period in Madagascar. A total of 114 cases were recorded during the study period. Mean patient age was 37 years. Patients were predominantly male. Pulmonary tuberculosis with positive bacilloscopy was the most common etiology (66.66%). Bronchopulmonary cancer accounted for only a small number of cases (1.75%). Etiology was undetermined in a significant number of cases (15.78%).